Waste Management By The Local Government of Ogan Ilir Regency (Case Study: In Timbangan Village) - Jeli Yana; Azizah Husin; Ardi Saputra (International Journal of Science and Environment (IJSE), 2025)
Waste management in Timbangan Village, Ogan Ilir Regency, faces various challenges such as low community discipline, limited final processing facilities, and a lack of sustainable waste utilization programs. This study aims to analyze the waste management process carried out by local governments and identify the factors that affect its effectiveness. With a qualitative approach through interviews and direct observations, data were collected from various relevant parties, including cleaners and environmental officials. The results showed that although the Temporary Shelter facilities were adequate and the waste collection was running quite efficiently, community behavior and final waste management were still suboptimal, causing environmental problems such as waste accumulation and health risks. It is suggested that the government increase public education, expand the use of waste management technology, and develop waste utilization programs such as waste banks and composting to create sustainable waste management. This study provides an important overview for improving waste management in other areas with similar challenges.